Strategy instruction, metacognitive training and attribution retraining : a combined approach for remediating secondary students' reading comprehension difficulties : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Horrex, Jan Erica (Massey University, 1992)
Students who adequately decode but have difficulty comprehending what they read, often possess a limited range of comprehension strategies. Furthermore, they often lack the metacognitive knowledge to use these strategies effectively. These two factors limit the likelihood of students experiencing success on a range of academic activities. As a consequence these students often develop dysfunctional attributional beliefs which also negatively impact on future learning. In the present study, 39 students with comprehension difficulties participated in an intervention programme comparing the effects of strategy-plus-attribution training, strategy-only training, and no training conditions on reading comprehension. The results revealed no significant improvement in students' reading comprehension. However, there was a significant improvement in students' use of comprehension strategies. A number of reasons have been suggested, which could explain why the increased use of strategies did not translate into improvements in reading comprehension. In light of these suggestions, several recommendations have been made regarding the future development and implementation of reading comprehension intervention programmes.
Keywords: Reading comprehension; Learning disabilities; Learning disabled children; Metacognition